2009
DOI: 10.1007/s00540-009-0781-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amitriptyline, a tricyclic antidepressant, on smooth muscle reactivity in isolated rat trachea

Abstract: Effects of amitriptyline, a tricyclic antidepressant, on smooth muscle reactivity of isolated rat trachea A short title: Amitriptyline and airway smooth muscle relaxation Key Words: Rats, Airway smooth muscle, Contractile response, Amitriptyline, Rho-kinase pathway, Phosphatidylinositol response 3 AbstractPurpose. This study was designed to investigate the action of amitriptyline, a tricyclic antidepressant, on airway smooth muscle reactivity and its underlying mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Matsunaga et al . showed that smooth muscle reactivity in isolated tracheal rings from rats was attenuated by amitriptyline incubation [ 36 ]. However, the concentrations of amitriptyline used by these authors in their study (> 1 µM) were in the higher µM range and partially toxic.…”
Section: Discussionmentioning
confidence: 99%
“…Matsunaga et al . showed that smooth muscle reactivity in isolated tracheal rings from rats was attenuated by amitriptyline incubation [ 36 ]. However, the concentrations of amitriptyline used by these authors in their study (> 1 µM) were in the higher µM range and partially toxic.…”
Section: Discussionmentioning
confidence: 99%
“…Amitriptyline inhibited the contractile responses of rat tracheal ring to SPC (10 μM): the concentration of amitriptyline (mean ± standard deviation) required to exert 50% inhibition (IC 50 ) was 98.2 ± 21.8 μM, respectively [172].…”
Section: Therapeutic Effects Of Spc and Spc Antagonistsmentioning
confidence: 99%
“…To evaluate the mechanism of FLX, muscle strips were incubated with each antagonist for 20 min and contraction was induced by EFS. They were then administrated with FLX and the inhibitory effect of FLX on EFS-induced muscle contraction was compared in the absence and presence of antagonists; L-NAME (10 µmol/l) [48], atropine (1 µmol/l) [49], guanethidine (10 µmol/l) [50], bicuculline (10 µmol/l), phacolfen (10 µmol/l), methysergide (100 µmol/l), ketanserin (1 µmol/l), ondansetron (1 µmol/l), GR 113808 (10 µmol/l) [49], nifedipine (1 µmol/l), calcium ionophore A23187 (1 µmol/l) [51], U73122 (1 µmol/l), chelerythrine (10 µmol/l), ML-9 (10 µmol/l), Y27632 (1 µmol/l) [52], TEA (10 mmol/l), 4-AP (100 µmol/l) and glybenclamide (10 µmol/l) [33]. Muscle strips were equilibrated for 30 min after washing with Kreb's solution for 3 times between each part within each sets of experiment.…”
Section: Methodsmentioning
confidence: 99%